(untitled) (Research, Society and Development, 2020)
Providing quality of life for patients with a disease that cannot be cured is a complex task that requires interdisciplinary planning with multiprofessional action. Objective: To describe the contributions of the dental surgeon to the palliative care team from an interdisciplinary perspective. Method: Search in the Virtual Health Library Brazil and selected the databases Medeline, LILACS, BBO and BDENF from 2013 to 2018. Results: In the search in the VHL were found 247 articles, after placing the filter of MEDLINE databases, LILACS, BDENF and BBO were obtained 232. When the filter of the year was placed, restricting the searches between 2013 and 2018, 69 articles were found. Conclusion: the findings underscored the importance of dentistry in the multidisciplinary palliative care team, considering that oral reactions that cause pain and difficulty feeding justify the participation of the dentist in the team for better patient comfort.